Джиттер искровых разрядников ЛТД; Известия вузов. Физика; Т. 58, № 9-2 - Ким А. А. Александр Андреевич; Синебрюхов В. А. Вадим Анатольевич; Алексеенко В. М. Виталий Михайлович; Кондратьев С. С. Сергей Сергеевич; Волков С. Н. Сергей Николаевич; Васильев С. В. Сергей Валериевич; Мазаракис М. Г. Майкл Герасим; Дейчули М. П. Михаил Петрович (2015, 2015)
Заглавие с экрана